Rethinking Education: A Case for Tarbiyah in Contemporary Britain - Shahin Rahman (Nazhruna: Jurnal Pendidikan Islam, 2020)
This paper explores solutions to the limitations of the purpose of education as currently understood and advocated in postmodern Britain. By adopting an interdisciplinary approach, it takes a closer look at the objectives of education as per another major civilization with a rich educational heritage–that is, the Islamic tradition–and compares the two distinct philosophies. The research finds that the contemporary British philosophy of education has several drawbacks due to focusing only on building the economy and shaping a political worldview. As such, this paper discusses how Britain might mitigate its current weaknesses by suggesting to integrate the Islamic model of education (tarbiyah) in order to foster personal development, civic engagement, and objectivity in research, learning, and producing new knowledge-without the need compromise its strong economy.